Texting Home: Examining the Mobile Phone Practices of Student Newcomers to Toronto - McEwan, Rhonda; Caidi, Nadia (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
We investigate the roles that new media play in supporting the relationships of young people in their first-year of university in Toronto. We consider the experiences of domestic and newly emigrated students and their adjustment to life outside their home countries, focusing on the use of social technologies for adjustment. Cette communication examine le rôle des nouveaux médias comme point d'ancrage relationnel des jeunes étudiants universitaires de première année à Toronto. Sont prises en considération les expériences d'étudiants locaux et étrangers ainsi que leur ajustement à la vie à l'extérieur de leur pays d'origine, avec une attention particulière à l'utilisation de technologies sociales comme médiateur de cet ajustement.